About a current cultural lag - Heidrun, Mollenkopf (Magyar Gerontológia, 2023)
At the beginning of the last century the American scientist Ogburn developed his theory of the "cultural lag". It is based on the observation that certain social developments, which are actually interrelated, can proceed at different speeds and behavioural or institutional framework conditions no longer fit in.